PENDALAMAN FITUR EVIEWS UNTUK MENGHASILKAN PUBLIKASI ILMIAH YANG BERKUALITAS BERSAMA ASOSIASI DOSEN MUDA INDONESIA (ADMI) - Tommy Kuncara; Zara Tania Rahmadi; Kampono Imam Yulianto; Abdul Muchlis (Jurnal Abdi Masyarakat Multidisiplin, 2022)
As a lecturer who has a Tri Dharma obligation, he is required to do community service, this is done by ADMI as an organization that does service to Gunadarma University lecturers. The purpose of this service is to introduce and use the features contained in the EVIEWS software as tools for analysis. Characteristics and level of knowledge of participants, in this case ADMI members in the EVIEWS in-depth training, methods and media and training materials available and used at ADMI, as well as teaching materials and media needed by ADMI members. This discussion was also carried out as a medium to equalize perceptions in determining methods as a reinforcement of the communicative Eviews in-depth training base and adding simulations regarding statistical analysis. The result we hope is to be able to help fellow human beings and be able to ease the burden of life for the community in terms of statistical needs that are used for work and daily life